Association between the introduction of a national targeted intervention program and the incidence of surgical site infections in Swiss acute care hospitals - Marcus Eder; Rami Sommerstein; Arlette Szelecsenyi; Alexander Schweiger; Matthias Schlegel; Andrew Atkinson; Stefan P. Kuster; Danielle Vuichard-Gysin; Nicolas Troillet; Andreas F. Widmer; for Swissnoso (Antimicrobial Resistance and Infection Control, 2023)
Abstract Background In Switzerland, the national surgical site infection (SSI) surveillance program showed a modest decrease in SSI rates for different procedures over the last decade. The study aimed to determine whether a multimodal, targeted intervention program in addition to existing SSI surveillance is associated with decreased SSI rates in the participating hospitals. Methods Prospective multicenter pre- and postintervention study conducted in eight Swiss acute care hospitals between 2013 and 2020. All consecutive patients > 18 years undergoing cardiac, colon, or hip/knee replacement surgery were included. The follow-up period was 30 days and one year for implant-related surgery. Patients with at least one follow-up were included. The intervention was to optimize three elements of preoperative management: (i) hair removal; (ii) skin disinfection; and (iii) perioperative antimicrobial prophylaxis. We compared SSI incidence rates (main outcome measure) pre- and postintervention (three years each) adjusted for potential confounders. Poisson generalized linear mixed models fitted to quarter-yearly confirmed SSIs and adjusted for baseline differences between hospitals and procedures. Adherence was routinely monitored through on-site visits. Results A total of 10 151 patients were included, with a similar median age pre- and postintervention (69.6 and IQR 60.9, 76.8 years, vs 69.5 and IQR 60.4, 76.8 years, respectively; P = 0.55) and similar proportions of females (44.8% vs. 46.1%, respectively; P = 0.227). Preintervention, 309 SSIs occurred in 5 489 patients (5.6%), compared to 226 infections in 4 662 cases (4.8%, P = 0.09) postintervention. The adjusted incidence rate ratio (aIRR) for overall SSI after intervention implementation was 0.81 (95% CI, 0.68 to 0.96, P = 0.02). For cardiac surgery (n = 2 927), the aIRR of SSI was 0.48 (95% CI, 0.32 to 0.72, P < 0.001). For hip/knee replacement surgery (n = 4 522), the aIRR was 0.88 (95% CI, 0.52 to 1.48, P = 0.63), and for colon surgery (n = 2 702), the aIRR was 0.92 (95% CI, 0.75 to 1.14, P = 0.49). Conclusions The SSI intervention bundle was associated with a statistically significant decrease in SSI cases. A significant association was observed for cardiac surgery. Adding a specific intervention program can add value compared to routine surveillance only. Further prevention modules might be necessary for colon and orthopedic surgery.